X-Aptamers: A bead-based selection method for random incorporation of drug-like moieties onto next-generation aptamers for enhanced binding - He, Weiguo (2012)
By combining pseudo-random bead-based aptamer libraries with conjugation chemistry, we have created next-generation aptamers, X-aptamers (XAs). Several X ligands can be added in a directed or random fashion to the aptamers to further enhance their binding affinities to the target proteins. Here we describe the addition of a drug (N-acetyl-2,3-dehydro-2-deoxyneuraminic acid) demonstrated to bind to CD44-HABD, to a complete monothioate backbone substituted aptamer to increase its binding affinity to the target protein by up to 23-fold, while increasing the drugs’ binding 1-million fold.